Preparation and Characterization of Nanocellulose from Ulva prolifera by Different Methods - Nan YANG; Lei WANG; Xin GAO; Jiachao XU; Xiaoting FU (Shipin gongye ke-ji)
Ulva prolifera, as the dominant species of the green macro-algal bloom, was used as the raw material to prepare cellulose (UPC) by alkali extraction and bleaching treatment with a yield of 23.61%. Nanocelluloses of UPCNC-S, UPCNC-H, and UPCNC-T were prepared using sulfuric acid hydrolysis, hydrochloric acid hydrolysis, and TEMPO oxidation methods, respectively. The structure and micro-morphology of the prepared nanocelluloses were characterized and compared based on yield, fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), particle size, zeta potential, and chromaticity value. The results showed that the yields of the nanocelluloses prepared by three methods were 10.07% of UPCNC-S, 32.48% of UPCNC-H, and 26.63% of UPCNC-T, respectively. All three methods did not damage the crystal form and the structure of the cellulose showed, an increase in crystallinity and reached 72.11% (UPCNC-S), 77.16% (UPCNC-H), and 66.53% (UPCNC-T). The thermal stability of nanocellulose UPCNC-S produced by sulfuric acid was to the weakest, while that of UPCNC-H was the optimal. In terms of morphological features, both UPCNC-T and UPCNC-H exhibited short-shaped morphology, with particle sizes concentrated around 430 nm and 610 nm, respectively. In addition to the short rod structure, partially spherical nanocellulose was produced by sulfuric acid hydrolysis, with the smallest particle sizes ranging from 300 nm to 400 nm. The Zeta potential values of the three types of nanocellulose were all less than −30 mV, indicating good stability in suspension. Besides, the color of UPCNC-S was slightly yellowish with the lowest whiteness value, while UPCNC-H and UPCNC-T both showed the whitish appearance. In summary, the nanocellulose prepared from Ulva prolifera in this study exhibited excellent characteristics such as high crystallinity, good dispersion, and small particle sizes, which would provide a theoretical basis for the high-value utilization of Ulva prolifera.